Subjective Quality of Vision before and after Cataract Surgery at Holy Family Hospital, Rawalpindi - Ali Raza, Muhammad Imran Janjua (Pakistan Journal of Ophthalmology, 2018)
Objective: To determine mean change in subjective quality of vision in patients undergoing cataract surgery at Holy Family Hospital, Rawalpindi. Study Design: Quasi experimental. Place and Duration of Study: Department of Ophthalmology, Holy Family Hospital, Rawalpindi, over a period of six months, from April, 2015 to October, 2015. Materials and Methods: 60 patients, between the age of 30 to 70 years with bilateral cataract diagnosed by slit lamp examination, undergoing cataract surgery with Phacoemulsification + IOL at Holy Family Hospital, Rawalpindi were included in this study. Patients were interviewed one day before surgery and their responses filled in the questionnaire. They were operated the next day by consultant Ophthalmologist and then followed up for one month for uneventful recovery after cataract surgery. The patients were interviewed again using the same questionnaire. The mean pre-operative and post-operative scores were compared. Results: A total of 60 patients were included in the study. Out of these 25 (41.7%) were males and 35 (58.3%) were females. The mean age was 56.15 ± 4.90 years (mean ± S.D). The right eye was operated in 32 (53.3%) patients and the left eye in 28 (46.7%). The average pre-operative score was 19.60 ± 2.12 (mean ± S.D). At one month, post-operatively the mean score was 29.68 ± 2.66 (mean ± S.D). There was an average difference of 10.08 ± 2.16 (mean ± S.D) between the pre and post-operative scores which was statistically significant (p = 0.00). Conclusion: Cataract surgery is an extremely effective and economical procedure, which has far greater implications for the lives of patients that cannot be measured on a visual acuity chart. Efforts should be made to educate people about the effectiveness and success of cataract surgery. Key Words: Cataract, Phacoemulsification, Subjective visual recovery.